Enhance Multi-factor Authentication Model for Intelligence Community Access to Critical Surveillance Data - Wan Muhamad, Wan Nurhidayat; Mat Razali, Noor Afiza; Ishak, Khairul Khalil; Hasbullah, Nor Asiakin; Mohd Zainudin, Norulzahrah; Ramli, Suzaimah; Wook, Muslihah; Ishak, Zurida; MSaad, Nurjannatul Jannah Aqilah (Advances in Visual Informatics, 2019)
Protection of critical data is one of the greatest challenges in any organization around the globe, especially for the intelligence community. Managing data, assets and resources require strong security method such as the authentication process that can guarantee only designated person will be receiving the required information. Any breach of information and assets could risk in the nation’s sovereignty and give significant impacts in social, political, economy and diplomacy or even lives. Authentication method enables intelligence data to be transferred covertly and the access to the system by a legitimate user is guaranteed, hence the elements of confidentiality, integrity, and availability of the data is assured. This study analyzed various authentication methods used to secure multiple platforms of data and system. This study serves as theoretical analysis on multi-factor authentication model for intelligence community access to critical surveillance data. This study aims to propose the enhance model that could be used as a basis to build a framework of the secured authentication system to avoid common attack on authentication and access management.